(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
A theme with a great interest in methodic literature is the problem of professional loyalty of the teacher in Bulgarian through measures in evaluation and expert, professional skills to expose the results of these actions to his subjects in proper form, according to lawful and national strategy. The present research analyses two types of action models of creating a reverse relation teacher-student in the written form (review). The material of 1857 reviews, created by 320 teachers from five regions in Bulgaria is researched by linguistic features (text features like line, cohesion, volume, forms of speech, grammar specific, composition and graphic) and linguistic didactic parallels (information, function, effect, loyalty). The results of two-years research of practice and transformation of used reverse relation in education in Bulgarian. The value of new strategy approaches and resultative models of such activity in the process of education in Bulgarian language and literature in Bulgaria. The article claims for responsibility from both sides of the educational process (teacher and students) according to relate evaluation activity to modern models of forming evaluation in order to better pedagogic communication in school and the results of it.